Carbon dynamics after thinning in two boreal forest sites: Upland and drained peatland - de Quesada, Gonzalo; Rautakoski, Helena; Xu, Jie; Li, Qian; Larmola, Tuula; Salovaara, Petri; Anttila, Vilma; Peltoniemi, Mikko; Koskinen, Markku; Lohila, Annalea; Aalto, Juho; Lehtonen, Aleksi; et al. (Elsevier, 2025)
Boreal forests act as crucial carbon storage, but their management can have important consequences for their carbon dynamics. Thinning of the stand alters carbon storage by removing trees, which affects the overall forest growth. Thinning stimulates growth of the remaining trees and affects soil processes in complex ways, while the overall impacts vary by forest type and site conditions. We applied biometric and soil CO2 flux measurement data to study the changes in carbon storage across multiple forest components in both an upland and a drained peatland forest undergoing thinning operations. Following thinning, the carbon accumulation rate of the aboveground biomass components declined sharply due to the removal of trees but started recovering a year after the thinning, largely driven by forest floor vegetation. Belowground biomass components followed a similar trend. Carbon emissions increased post-thinning, mainly due to decomposition of harvest residues. The upland forest net ecosystem production (NEP) temporarily shifted to a net source of carbon (-43 g C m⁻² yr⁻¹) but it recovered the following year to a net carbon sink (164 g C m⁻² yr⁻¹). The drained peatland forest NEP remained negative, with thinning further increasing the CO2 emissions (-570 g C m⁻² yr⁻¹) and leading to a slow recovery (-488 g C m⁻² yr⁻¹) to pre-thinning levels. The tree carbon stocks in both forest type is projected to take over a decade to recover. The effects of thinning on forest carbon dynamics show short-term changes in the upland forest but more lasting consequences in the drained peatland forest due to slower tree growth and persistent emissions.
Keywords: forest management; thinning; carbon budget; net ecosystem production; carbon balance; boreal forest